Letter - Halifax, Edward Frederick Lindley Wood, Earl of, 1881-1959
012b-0011-001 Foreign Office, S.W.1. 15th September, 1939. Dear Sir Walter, Thank you very much for your letter of the 13th September asking whether it would be possible to intercede in favour of Jose Rodriguez Vega. We are bringing this case to the notice of our Ambassador in Spain, asking him to do anything which may be possible in Senor Vega's favour. At the same time, I feel I must warn you that it is very difficult for Sir Maurice Peterson to intervene and that in previous similar cases he has felt that any intervention on his part would do more harm than good. Nevertheless, I am sure that he will do anything he feels he can in this case. Yours sincerely, Halifax Sir Walter Citrine, K.B.E. 292/946/12b/11